Revitalizing Mangrove Botanical Garden Ecotourism in Surabaya Through Bamboo Fencing Innovation to Mitigate Coastal Abrasion - Maulida, Rizqa; Prameswari, Kania Intan Putri (Politeknik Negeri Bandung, 2025)
Global climate change continues to significantly impact coastal ecosystems, particularly mangrove forests significantly, which are critical in maintaining ecological stability and protecting coastal areas from erosion. The Surabaya Mangrove Botanical Garden, Indonesia's only mangrove botanical garden, is increasingly vulnerable to coastal abrasion due to rising sea levels and the intensification of extreme weather events. This study explores the potential application of bamboo fencing as an environmentally friendly innovation to mitigate coastal erosion and revitalize ecotourism in the area. Utilizing a literature-based method, this research evaluates the effectiveness of bamboo barriers in reducing wave energy, facilitating sediment deposition, and enhancing mangrove regeneration. The findings indicate that bamboo fences serve as a natural coastal defense mechanism, strengthening shoreline resilience, supporting ecosystem sustainability, and promoting conservation-based ecotourism. Furthermore, this initiative aligns with the United Nations Sustainable Development Goals (SDGs), particularly Goal 13 (Climate Action) and Goal 15 (Life on Land), by integrating nature-based solutions into coastal management strategies.